Gender Equality in North Cyprus (Turkish Republic Of North Cyprus) - Güven - Lisaniler, Fatma (Quaderns De La Mediterrania, Periodical Publication Of IEMed (Institute Europeu De La Mediterranie), 2006)
[Abstract Not Available]
Keywords: Gender Equality - Cyprus, North; Gender Inequality; Women Rights